Digital Marketing Strategy to Increase Sales Through Social Media at Oriflame Jogja Resellers is Viewed From the Concept of Sharia Marketing - May Shinta Retnowati; Andini Rachmawati; Muhammad Faruq Averro (Ijtihad, 2023)
*English* In general, the marketing pattern applied by business actors is only profit-oriented, leaving the priority of empowerment and education for the community. In the current era of globalization, the business and economic world faces great challenges.  Technological progress is inevitable. Islam of course also regulates how to do business properly and correctly. In the Islamic business, marketing procedures are also considered to be in accordance with the rules as well as those applied by Oriflame Resellers Jogjakarta using marketing that is classified as traditional such as the printed catalog, Oriflame Resellers change the concept of marketing management by using the help of information technology and communication through social media. This study uses qualitative methodology that will produce descriptive data consisting of observed behavior, interviews, and documentation. The result of this research is that Oriflame Jogjakarta resellers use interaction between individuals through their respective social media accounts or what is called personal selling or individually resellers introduce products needed by consumers. While the sale of resellers' products still raises the wasteful nature of consumers, this is also supported by social media that makes it easier for consumers to get the desired product even though it is not needed.                                                                                                                  *Indonesia* Pada umumnya, pola pemasaran yang diterapkan oleh pelaku usaha hanya berorientasi terhadap profit belaka, dengan meninggalkan keutamaan pemberdayaan dan edukasi bagi masyarakat. Era globalisasi saat ini, dunia bisnis dan ekonomi menghadapi tantangan yang besar.  Kemajuan teknologi menjadi hal yang tidak dapat dihindari. Islam tentunya juga mengatur cara berbisnis dengan baik dan benar. Dalam bisnis islam tatacara pemasaran juga diperhatikan agar sesuai dengan kaidah begitu juga yang diterapkan oleh Reseller Oriflame Jogjakarta menggunakan pemasaran yang tergolong tradisional seperti katalog cetak tersebut, Reseller Oriflame mengubah konsep pengelolaan pemasaran dengan menggunakan bantuan teknologi informasi dan komunikasi melalui media sosial. Pada konsep pemasaran yang dilakukan oleh Oriflame, bagaimana Islam meninjau praktik pemasaran tersebut. Pada penelitian ini menggunakan metodologi kualitatif yang akan menghasilkan suatu data deskriptif terdiri dari prilaku seseorang yang diamati, wawancara, dan dokumentasi. Adapun hasil dari penelitian ini adalah  reseller Oriflame Jogjakarta menggunakan interaksi antar individu melalui akun social media mereka masing-masing atau yang disebut dengan personal selling atau secara individu reseller mengenalkan produk-produk yang dibutuhkan oleh konsumen. sedangkan pada penjualan produk para reseller masih memunculkan sifat boros konsumen, hal ini juga didukung dengan media sosial yang memudahkan konsumen untuk mendapatkan produk yang diinginkan walaupun tidak dibutuhkan.